THE ROLE OF PULSE PRESSURE IN NAVIGATING THE PARADIGM OF CHRONIC KIDNEY DISEASE PROGRESSION IN TYPE 2 DIABETES - Low, Serena; Lim, Su Chi; Ang, Keven; Tang, Wern Ee; Kwan, Pek Yee; Subramaniam, Tavintharan; Sum, Chee Fang (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Arterial stiffness is a risk factor for chronic kidney disease (CKD) progression. Alterations in pulse wave velocity (PWV), a measure of arterial stiffness, lead to increased systolic blood pressure (SBP) and decreased diastolic blood pressure (DBP) known as pulse pressure (PP). It is unclear if PP predicts CKD progression in Type 2 Diabetes (T2D). METHODOLOGY This was a prospective study of 1,494 patients with estimated glomerular filtration rate ≥15 ml/min/1.73 m2 from SMART2D cohort. Carotid-femoral PWV was measured by applanation tonometry. PP was calculated as difference between SBP and DBP. CKD progression was defined as deterioration across KDIGO estimated glomerular filtration rate (eGFR) categories with ≥25% drop from baseline. RESULTS After follow-up of up to 6 years, CKD progression occurred in 33.5% of subjects. Cox regression showed a dose-dependent relationship between PP and CKD progression with hazards ratio (HR) 1.36 (95%CI 1.01-1.84; p=0.004), 2.41 (1.85-3.15; p<0.001) and 3.14 (2.43-4.06; p<0.001) for quartiles 2, 3 and 4 respectively in unadjusted analysis. Having adjusted for demographics and clinical covariates, the association persisted for quartiles 3 and 4 with HRs 1.66 (1.25-2.20; p<0.001) and 1.76 (1.32-2.36; p<0.001) respectively. There was no significant difference between PP and PWV alone in receiver-operating curve for CKD progression (65.5% vs. 67.5%; p=0.246). Binary mediation analysis revealed that urinary albumin-to-creatinine ratio accounted for 48.3% of the association between PP and CKD progression. CONCLUSION Individuals with high PP were susceptible to deterioration of renal function. Albuminuria partially contributed to the pathophysiological mechanism. PP could potentially be incorporated in clinical practice as an inexpensive and convenient marker of renal decline in T2D.